Whistleblowing Among Auditors in Bandung: An Islamic-Based Perspective on Professional and Ethical Motivations - Sri Suharti; Tsania Wandari; Bagus Cakti Dwi Nursetiaji Mas (Fakultas Ekonomi dan Bisnis Islam, 2024)
In the context of Maqasid al-Shariah, whistleblowing serves as a mechanism to stop unethical behavior, especially financial corruption, which has increased significantly in recent years. The purpose of this study is to examine the factors that motivate auditors working in public audit offices in Bandung to whistleblow. Due to its status as one of Indonesia's economic centers, Bandung was chosen as the research location. It offers contextually relevant and distinctive information that enhances the research. Using a quantitative approach with descriptive and verification methods, this study examines the influence of professionalism (X1), commitment (X2), and moral intensity (X3) on auditors reporting violations. (Y). Initial data were collected using questionnaires and structured analysis, and then analyzed using multiple regression analysis and SPSS software. The findings indicate that professionalism, locus of commitment, and moral intensity significantly and simultaneously influence auditors' motivation to engage in whistleblowing.